2018
DOI: 10.1186/s41021-017-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Increase of somatic cell mutations in oxidative damage-sensitive drosophila

Abstract: BackgroundOxidative damage is an important genotoxic source for almost all organisms. To efficiently detect mutations induced by oxidative damage, we previously developed a urate-null Drosophila strain. Using this Drosophila strain, we showed the mutagenic activity of environmental cigarette smoke (ECS) and the herbicide paraquat, which are known to produce reactive oxygen species (ROS). In the present study, we examined the mutagenic activities of carcinogenic mutagens that are considered to cause mutations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The lack of mutagenic activity further supports that apoptosis is not a mechanism for the inhibition of MCF-7 cells growth, since mutated cells will normally go into apoptosis. Moreover, ROS were not detected on cells exposed to EP, which is also consistent with EP’s absence of mutagenic activity, since ROS are recognized for their mutagenic activity [16, 36].…”
Section: Discussionsupporting
confidence: 57%
“…The lack of mutagenic activity further supports that apoptosis is not a mechanism for the inhibition of MCF-7 cells growth, since mutated cells will normally go into apoptosis. Moreover, ROS were not detected on cells exposed to EP, which is also consistent with EP’s absence of mutagenic activity, since ROS are recognized for their mutagenic activity [16, 36].…”
Section: Discussionsupporting
confidence: 57%
“…PhIP might be generating ROS by more than one mechanism, which would induce DNA damage and cell toxicity 39 . ROS was generated from MeIQx and the ROS might be involved in mutagenesis 40 . An early study demonstrated that TDA can lead to cytotoxicity and oxidative DNA damage through the induction of ROS at concentrations from 50 to 200 μM in A549 cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…PhIP might be generating ROS by more than one mechanism, which will induce DNA damage and cell toxicity 38 . ROS was generated from MeIQx and the ROS might be involved in mutagenesis 39 . An early study demonstrated that TDA can lead to cytotoxicity and oxidative DNA damage through the induction of ROS at concentrations from 50-200 µM in A549 cells 40 .…”
Section: Discussionmentioning
confidence: 99%